2012
DOI: 10.1038/oby.2011.49
|View full text |Cite
|
Sign up to set email alerts
|

CRP Is Related to Higher Leptin Levels in Minority Peripubertal Females Regardless of Adiposity Levels

Abstract: Overweight is related to higher levels of C-reactive protein (CRP) and leptin, which have been independently associated with increased risk for diabetes, cardiovascular disease, and the metabolic syndrome. Elevated CRP may trigger leptin resistance by inhibiting the binding of leptin to its receptors. We cross-sectionally examined the relationship between CRP, leptin, BMI z-score, percent body fat (%BF) assessed by air plethysmography (BodPod), and insulin sensitivity (SI) and acute insulin response (AIRg) mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
0
15
2
Order By: Relevance
“…Specifically, studies have shown that obesity is associated with a state of chronic low-grade inflammation that is correlated with decreased insulin sensitivity and impaired glucose metabolism [58•, 59•, 60, 61, 62]. Although it was once believed that adipose tissue was only involved in the storage of free fatty acids as triglycerides, it is now recognized that this tissue also acts as a dynamic endocrine organ, contributing to the chronic-low grade inflammation seen during obesity.…”
Section: Adipose Tissue Inflammation and Fibrosismentioning
confidence: 99%
“…Specifically, studies have shown that obesity is associated with a state of chronic low-grade inflammation that is correlated with decreased insulin sensitivity and impaired glucose metabolism [58•, 59•, 60, 61, 62]. Although it was once believed that adipose tissue was only involved in the storage of free fatty acids as triglycerides, it is now recognized that this tissue also acts as a dynamic endocrine organ, contributing to the chronic-low grade inflammation seen during obesity.…”
Section: Adipose Tissue Inflammation and Fibrosismentioning
confidence: 99%
“…CRP has been shown to contribute to as much as 10% of the variance in leptin levels (Spruijt-Metz et al, 2012). CRP also impairs the cellular response to leptin in vascular endothelial cells, thus is mechanistically linked to the development of leptin resistance (Procopio et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown to induce a form of leptin resistance (Procopio et al, 2009), which partly explains the relationship between leptin and CRP that is independent of adiposity (Spruijt-Metz et al, 2012). Exercise training does not always lower CRP , but we hypothesize that any reduction in leptin as a result of exercise training may be influenced by an initially elevated CRP level.…”
mentioning
confidence: 97%
“…Hyperleptinemia is associated with low-grade inflammation and metabolic dysregulation manifested by high levels of CRP, TNF-a, IL-10, IL-12, glucose, insulin, and TGs and high IR values in obese mice and humans [259]. On the contrary, it has been shown that leptin does not underlie the pro-inflammatory condition in obese human subjects [260,261]. Leptin enhances the secretion of IL-18 (implicated in T2DM complications) from monocytes via activation of caspase-1 inflammasome [262].…”
Section: Leptinmentioning
confidence: 96%